Stereochemistry conformations and asymmetric synthesis : Problem solving approach - Jena, Satyaban; Rout, Laxmidhar (New Delhi: Indu book service, 2024)
There are five chapters in the book starting from scratch to complex level. Chapter 1 is started with problems on Conformational analysis & Reactivity. Chapter 2 deals with Conformation & diastereoselective reactions. Chapter 3 covers all rules and principles of Stereochemistry. Chapter 4 is related to Enantiodiscrimination and resolutions. Chapter 5 is related to problems of Asymmetric Synthesis.
Includes appendix
Keywords: Stereochemistry -- Molecular structure -- Asymmetric synthesis